The Power of Stories to Build Partnerships and Shape Change - Deborah Romero (The University of Alabama, 2022)
This essay reflects on the power of storytelling and narrative in a collaborative partnership that engaged undergraduate pre-service English as Second Language (ESL) candidates and their professor with local ESL high school teachers, immigrant and refugee students, and their families. It describes how undergraduate students worked with teachers and students to collect stories and publish a multilingual book about their journeys, memories of home, and transitions into their new life in the United States. This project and the resulting self-published book, which was shared at several community and public events, exemplify the fundamentals of reciprocal and transformative partnerships. The nature and importance of such partnerships are examined, including recommendations for similar undertakings, and a discussion about how the book students and families were empowered by sharing their voices. It closes by examining how the book became a tangible means to transcend the initial partnership and to promoting new understandings and relationships through sustained community engagement.